The transported active mulberry leaf phenolics inhibited adipogenesis through PPAR‐γ and Leptin signaling pathway. Issue 10 (15th June 2022) - Li, Qian; Liao, Sentai; Pang, Daorui; Li, Erna; Liu, Tongxian; Liu, Fan; Zou, Yuxiao
Abstract: The effective components of mulberry leaf polyphenols (MLPs) should be absorbed and transported by the intestinal cells before regulating lipid metabolism. The Caco‐2 intestinal epithelial cell and 3 T3‐L1 adipocytes were coupled to screen the effective components of MLPs that are being absorbed and transported by intestinal cells. The regulation and molecular mechanism by which the effective components affect adipogenesis were analyzed in this study. Among the 12 main components identified, five main compounds were well absorbed with Papp in the order of benzoic acid > chlorogenic acid > astragaloside > hyperoside > rutin. Chlorogenic acid and benzoic acid were mainly absorbed through passive diffusion, while rutin, astragaloside, and hyperoside were mainly by active transport, of which chlorogenic and rutin absorption were mediated by the efflux protein, P‐glycoprotein (P‐pg). Based on the transport volume of 2 mg/ml MLPs within 2 h, 25% of the maximum transported MLPs (TMLPs) was a safe concentration for 3 T3‐L1 preadipocytes. Except for astragaloside, the other four components showed a significant inhibitory effect on lipid droplets, TG and TC, and chlorogenic acid and benzoic acid had the strongest effect. Additionally, we observed a synergistic effect as TMLPs were the most effective. We hypothesized that TMLPs, chlorogenic acid and benzoic acid suppressed adipogenesis and regulated lipid metabolism by inhibiting PPAR‐γ, C/EBP‐α, and FAS mRNA while promoting ADIPO and Leptin mRNA expression. Practical applications: The absorption and adipogenesis inhibition effect of mulberry leaf phenolics were evaluated in this study. The results provided guideline for the development of functional foods in regulating lipid metabolism. Abstract : Pathways and mechanism by which MLPs inhibit adipogenesis.